Empowering Micro and Small Enterprises Legal for Halal Certification in Tajungan Village Kamal Bangkalan - Indah Purbasari; Murni Murni; Azizah Azizah; Faris Hamidi; Qolbian Rohim (Community Development Journal, 2023)
Halal Certificate is one of the obligations of businessmen regulated in Law Number 33 of 2014 concerning Guarantees for Halal Products. This law obliges all commodities circulating in Indonesia must be halal certified, including products of micro and small enterprises. Therefore, this community service program was carried out with the aim of socializing the mandatory of halal certification with the target of micro and small business enterprisers in Tajungan Village, Kamal District, Bangkalan Regency. The ultimate goal is the registration of halal certificate for micro business products in the region. The program applied education method by conducting separately the halal product processing trainings both for Universitas Trunojoyo Madura students in order to be certified halal counselors and micro and small enterprisers. The counselling for Halal Product Processing was carried out by gathering micro and small enterprisers at the Tajungan Village Office, Kamal District, Bangkalan Regency. They were educated to make them convince toward the urgency of halal certification, to persuade them for applying for halal certification through the self-declaration mechanism at which free of charge and to assist them directly in registering halal certificate. This program was warmly welcomed by women micro and small enterprisers in Tajungan Village because most of them were on average less educated but they were eager to obtain halal product certificates. As the result, the students’ counselors succeeded in legally registering ten micro and small enterprisers in Online Single Submission (OSS) website and registered their products to receive halal certificate through sihalal website. Therefore, halal education for micro and small enterprisers must still be carried out to encourage their desire to become part of the halal product guarantee system that is obliged by the law.